The Effect of p.Arg25Cys Alteration in NKX2-5 on Conotruncal Heart Anomalies: Mutation or Polymorphism? - Akçaboy, M. İ.; Cengiz, F. B.; İnceoğlu, B.; Uçar, T.; Atalay, S.; Tutar, E.; Tekin, M. (Pediatric cardiology, 2008)
Heterozygous mutations in the NKX2-5 gene of patients with various congenital heart defects have been reported. Most of the congenital heart defects associated with the mutations in the NKX2-5 gene are conotruncal heart anomalies, primarily the tetralogy of Fallot. In this study, the authors screened 72 Turkish children with conotruncal heart anomalies and 185 healthy control subjects to find the NKX2-5 alterations. They found one previously documented NKX2-5 missense alteration, heterozygous c.73C>T (p.Arg25Cys), in a 10-year-old boy with tetralogy of Fallot. The same heterozygous alteration was found also in the patient’s healthy father and in two unrelated persons in the healthy control group. The current study shows for the first time the presence of p.Arg25Cys in healthy control subjects other than African Americans. These results show that no genetic support exists for the pathogenecity of this alteration, although a previous in vitro study and theoretical predictions suggest a structural/functional difference in the altered protein region.